2022
DOI: 10.3389/fnagi.2022.946509
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ankle inversion proprioception during walking is associated with fear of falling in older adults

Abstract: BackgroundAnkle proprioception plays a critical role in lower limb movement control. However, the relationship between ankle proprioception and fear of falling (FOF) in older people is still unclear.Objective(1) This study aims to develop a new device for measuring ankle inversion proprioceptive discrimination sensitivity during walking, i.e., the Ankle Inversion Discrimination Apparatus–Walking (AIDAW), and assess the test–retest reliability of the AIDAW in both young and older adults; (2) to evaluate the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Our ndings con rmed that musculoskeletal pain was signi cantly associated with risk of falls, aligning with similar reports in studies of other populations involving different pain sites [21,23,24,[31][32][33]. A number of speci c pain sites can increase the risk of falls particularly in older people.…”
Section: Musculoskeletal Pain In Uencing Risk Of Fallssupporting
confidence: 90%
See 1 more Smart Citation
“…Our ndings con rmed that musculoskeletal pain was signi cantly associated with risk of falls, aligning with similar reports in studies of other populations involving different pain sites [21,23,24,[31][32][33]. A number of speci c pain sites can increase the risk of falls particularly in older people.…”
Section: Musculoskeletal Pain In Uencing Risk Of Fallssupporting
confidence: 90%
“…For example, people experiencing waist pain often have impaired central proprioceptive processing and decreased ankle proprioception, which can result in underestimating the extent of ankle inversion and a fall [31,32]. Pain in the waist and lower limbs including leg, knee, and ankle can also in uence lower limb proprioception, muscle strength, joint stability, reactive balance, and fear of falling, all of which may increase falls risk [21,23,24,33]. Interestingly and different to other studies, we found a signi cant relationship between nger pain and the incidence of falls in our study population.…”
Section: Musculoskeletal Pain In Uencing Risk Of Fallsmentioning
confidence: 99%
“…Musculoskeletal pain in uencing risk of falls Our ndings con rmed that musculoskeletal pain was signi cantly associated with risk of falls, aligning with similar reports in studies of other populations involving different pain sites [20,22,23,[30][31][32]. A number of speci c pain sites can increase the risk of falls particularly in older people.…”
Section: Individual Factors In Uencing Risk Of Fallssupporting
confidence: 87%
“…For example, people experiencing waist pain often have impaired central proprioceptive processing and decreased ankle proprioception, which can result in underestimating the extent of ankle inversion and a fall [30,31]. Pain in the waist and lower limbs including leg, knee, and ankle can also in uence lower limb proprioception, muscle strength, joint stability, reactive balance, and fear of falling, all of which may increase falls risk [20,22,23,32]. Interestingly and different to other studies, we found a signi cant relationship between nger pain and the incidence of falls in our study population.…”
Section: Individual Factors In Uencing Risk Of Fallsmentioning
confidence: 99%
“…In order to calculate the AIDAW proprioceptive discrimination sensitivity score, the raw data of the 40 randomly assigned ankle inversion positions and their associated participant responses were entered into a 4 4 matrix representing the frequency with each response was made to each stimulus. Then the true positive rate (sensitivity) and the false positive rate (1-specificity) were calculated ( Shao et al, 2022 ). The ROC curve is the plot of sensitivity against specificity.…”
Section: Methodsmentioning
confidence: 99%